2009
DOI: 10.2174/1876214x00902010130
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigations of Ruthenium(III) Catalyzed Oxidation of L-Tryptophan by Diperiodatocuprate(III) in Aqueous Alkaline Media (Stopped Flow Technique): A Kinetic Study

Abstract: The kinetics of the oxidation of ruthenium(III) (Ru(III)) catalyzed oxidation of L-tryptophan (L-trp) by diperiodatocuprate(III) (DPC) in aqueous alkaline medium at a constant ionic strength of 0.20 mol dm-3 was studied spectrophotometrically. The reaction between L-tryptophan and DPC in alkaline medium in presence of [Ru(III)] exhibits 1:4 stoichiometry (L-trp:DPC). The reaction was of first order in [DPC], less than unit order in [L-trp] and negative fractional order in both [OH-] and [IO 4-]. The order in [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Other products were identified as discussed elsewhere [31,44]. Similar oxidation products with different experimental conditions have been also reported earlier [33][34][35][36]. On the other hand, the formation of Cr III species was confirmed by the decrease in the oxidation rate upon addition of manganese(II) sulfate to the reaction mixture [14,20].…”
Section: Stoichiometry and Product Analysissupporting
confidence: 77%
See 2 more Smart Citations
“…Other products were identified as discussed elsewhere [31,44]. Similar oxidation products with different experimental conditions have been also reported earlier [33][34][35][36]. On the other hand, the formation of Cr III species was confirmed by the decrease in the oxidation rate upon addition of manganese(II) sulfate to the reaction mixture [14,20].…”
Section: Stoichiometry and Product Analysissupporting
confidence: 77%
“…There is also an indication that some amino acids may play an important role in the chemistry of chromium, especially in the environment, where Cr V1 may present a serious hazard because of its mutagenic and carcinogenic activity [1][2][3]. They have been oxidized by a variety of reagents under different experimental conditions and they often undergo oxidative decarboxylation and deamination [24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of kinetic investigations on the oxidation of amino acids are being carried out using various oxidants under different experimental conditions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] because of their biological significance, selectivity towards the oxidants and to understand the mechanism of such biological redox reactions. In many cases, [5][6][7][8][9][10][11][12][13][14] it was reported that amino acids undergo oxidative decarboxylation and deamination. L-Tryptophan (Trp) is one of the essential amino acids that is required in human diet.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years either alone or binary mixtures, the use of transition metal ions, as catalysts in various redox processes have attracted considerable interest [28]. For different metal ion catalysts like Cr(III) [29], Ru(III) [30][31][32][33][34][35][36][37][38][39][40], Ir(III) [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], Pd(II) [52,[56][57][58][59] and Os(VIII) [59][60][61][62][63], Au(II) [64] different oxidizing agents have been used in the oxidation of organic compounds. The mechanism of the reaction relies upon the nature of the substrate, oxidant and moreover upon the ways in which transition metal complex ions play their role in order to promote the reactant molecules to the activated state before finally changing into products under experimental conditions.…”
Section: Introductionmentioning
confidence: 99%